2020
DOI: 10.1038/s42003-020-0922-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomes of the human skin reveal age-related loss of fibroblast priming

Abstract: Fibroblasts are an essential cell population for human skin architecture and function. While fibroblast heterogeneity is well established, this phenomenon has not been analyzed systematically yet. We have used single-cell RNA sequencing to analyze the transcriptomes of more than 5,000 fibroblasts from a sun-protected area in healthy human donors. Our results define four main subpopulations that can be spatially localized and show differential secretory, mesenchymal and pro-inflammatory functional annotations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
330
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(387 citation statements)
references
References 64 publications
26
330
2
4
Order By: Relevance
“…When combined with gene ontology analysis, fibroblast heterogeneity by expression of SFRP2, FMO1, and COL11A1 was associated with regulating signaling pathways, matrix deposition, as well as possibly serving as pluripotent mesenchymal cells (Philippeos et al, 2018;Tabib et al, 2018). Similar functional and spatial heterogeneity has been demonstrated in murine fibroblast populations (Joost et al, 2020;Salzer et al, 2018) and more comprehensively defined in a recent larger study of human skin (Solé-Boldo et al, 2020). Analysis of full-thickness murine anagen and telogen skin has further shown that dermal fibroblasts exhibit distinct transcriptional states correlating to hair cycle stage (Joost et al, 2020).…”
Section: Understanding Skin Biology In Health and Diseasesupporting
confidence: 53%
See 1 more Smart Citation
“…When combined with gene ontology analysis, fibroblast heterogeneity by expression of SFRP2, FMO1, and COL11A1 was associated with regulating signaling pathways, matrix deposition, as well as possibly serving as pluripotent mesenchymal cells (Philippeos et al, 2018;Tabib et al, 2018). Similar functional and spatial heterogeneity has been demonstrated in murine fibroblast populations (Joost et al, 2020;Salzer et al, 2018) and more comprehensively defined in a recent larger study of human skin (Solé-Boldo et al, 2020). Analysis of full-thickness murine anagen and telogen skin has further shown that dermal fibroblasts exhibit distinct transcriptional states correlating to hair cycle stage (Joost et al, 2020).…”
Section: Understanding Skin Biology In Health and Diseasesupporting
confidence: 53%
“…This may imply a key function of Wnt signaling between basal KCs and papillary dermal fibroblasts (Philippeos et al, 2018). Novel insights into skin aging highlight age-related loss of fibroblast cellular identity with alteration in functional and spatial gene expression signatures, which may be altered by dietary and metabolic interventions (Salzer et al, 2018;Solé-Boldo et al, 2020).…”
Section: Understanding Skin Biology In Health and Diseasementioning
confidence: 99%
“…To date, this approach has been applied to brain 31 , 32 , heart 33 , 34 , kidney 35 37 , liver 38 , 39 , lungs 40 43 , placenta 29 , 30 , 44 , retina 45 and visual cortex 46 . Remarkably, this approach revealed new roles of cells within a tissue 41 and helped explain how ageing 32 , 47 , diseases 34 36 , 48 51 , infections 52 and injuries 31 , 40 , 43 shape multicellular organization. Intercellular crosstalk has been investigated in healthy and diseased liver 50 , kidneys during homeostasis and rejected kidney transplants 35 , 36 , heart during failure and recovery conditions 34 , and healthy and asthmatic lungs 51 .…”
Section: Insights From Rna-based CCI Analysesmentioning
confidence: 99%
“…A similar study distinguished five mesenchymal populations, which were described as upper and lower dermal fibroblasts, pericytes and two uncharacterised populations [23•]. Comparing young and old human skin in an extensive RNA-seq analysis Solé-Boldo et al, identified four major dermal fibroblast populations with functionally distinct transcriptomic signatures and spatial distribution and defined these as secretory-reticular, secretory-papillary, pro-inflammatory and mesenchymal fibroblasts [24]. Notably, another RNA-seq study mapping six distinct fibroblast populations in human skin failed to correlate established human papillary and reticular fibroblast markers to any specific clusters [25].…”
Section: Fibroblast Heterogeneity In Development Homeostasis and Fibmentioning
confidence: 99%